Early segmental relaxation abnormalities in hypertrophic cardiomyopathy for differential diagnostic of patients with left ventricular hypertrophy. Issue 11 (24th July 2017) - Voigt, Christian; Münch, Julia; Avanesov, Maxim; Suling, Anna; Witzel, Katrin; Lund, Gunnar; Patten, Monica
Abstract : Background: Hypertrophic cardiomyopathy (HCM) is characterized by asymmetric left ventricular hypertrophy (LVH). However, clinical signs can be subtle and differentiation from other causes of LVH is challenging. Hypothesis: As diastolic dysfunction (DD) is an early sign in HCM, we aimed to find regional changes in relaxation pattern for differentiation from other entities of LVH. Methods: In 148 patients (81 HCM, 55 arterial hypertension (AHT), 12 Fabry disease) and 63 healthy controls, relaxation patterns were assessed using regional tissue Doppler imaging. In 42 HCM patients, myocardial mass and fibrosis were quantified by cardiac magnetic resonance imaging and correlated with relaxation parameters. Results: In HCM the septal to lateral isovolumic relaxation time (s/l IVRT) ratio was higher (1.5 ± 0.4) compared with AHT (1.1 ± 0.2), Fabry disease (1.0 ± 0.1), and controls (1.1 ± 0.2; P < 0.001), showing 77% sensitivity and 79% specificity to discriminate HCM‐related LVH from other entities. The s/l IVRT ratio was independent of global DD in HCM (HCM with DD: 1.5 ± 0.5, n = 52; HCM without DD: 1.5 ± 0.3, n = 29) and remained significantly different from other entities in a subgroup of HCM patients with maximum wall thickness < 20 mm (s/l ratio: 1.5 ± 0.5, n = 28). Regional IVRT did not correlate with the corresponding segmental myocardial mass or amount of fibrosis in cardiac magnetic resonance imaging. Conclusions: HCM patients show a prolonged septal IVRT irrespective of the extent of LVH and even before developing global DD. The s/l IVRT ratio is significantly higher in HCM compared with AHT or Fabry disease, thus establishing segmental IVRT analysis as a potential parameter for differential diagnosis in LVH.